2023
DOI: 10.1039/d2ob02292c
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new synthetic method for oligodeoxynucleotides using 3′-H-phosphonamidate derivatives

Abstract: In this study, we developed a new approach for the solution-phase synthesis of oligodeoxynucleotides (ODNs) using nucleoside 3ʹ-H-phosphonamidate derivatives as monomers. The H-phosphonamidate monomers having a heterocyclic amino group as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…H -Phosphonamidate 1 was synthesized following our previously reported procedure. 9 Next, we activated the thiomorpholino group of H -phosphonamidate monomer using various acidic activators. The 1.2 equivalents of H -phosphonamidate 1 were condensed with 2 bearing the 5′-OH group using acidic activators.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…H -Phosphonamidate 1 was synthesized following our previously reported procedure. 9 Next, we activated the thiomorpholino group of H -phosphonamidate monomer using various acidic activators. The 1.2 equivalents of H -phosphonamidate 1 were condensed with 2 bearing the 5′-OH group using acidic activators.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study revealed that this sulfurization reaction proceeded instantly to yield the stable phosphorothioate diester 8 and phosphorothioamidate monoester derivative 9 from H -phosphonate diester 3 and H -phosphonamidate monomer 1, respectively. 9 Therefore, the condensation efficacy can be determined via the 31 P NMR analysis of the reaction mixture after sulfurization. The results are shown in Table 5 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations